Comparative Morpho-Anatomical Studies of two Philippine Endemic Species of Amyema Tiegh. (Loranthaceae) - Romeo M. Tubongbanua; Noe P. Mendez; Victor B. Amoroso (Tropical Life Sciences Research, 2023)
Amyema are epiphytic hemiparasitic plants on different types of woody host plants and are abundant in temperate, subtropical, and tropical regions. In Marilog Forest Reserve, Southern Philippines, two Philippine endemic species of Amyema were recorded, viz., Amyema curranii (Merr.) Danser and A. seriata (Merr.) Barlow. In this study, these two species were compared and examined for their morphology and anatomy. Data revealed that the two Amyema species are morphologically distinct, with A. curranii having lanceolate leaves, pink flowers and red fruits, whereas A. seriata has obovate leaves, red flowers, and red fruits. For the morpho-anatomy, A. curranii has a single-layered epidermis, paracytic stomata, collateral open vascular bundles, the Eustele type of stele with pith at the centre, and the inferior free central type with a hairy ovary wall. Meanwhile, A. seriata has a pinkish, single-layered epidermis, paracytic stomata, collateral open vascular bundles, a eustele type of stele with the presence of pith at the centre, and an inferior free central ovary type. As a result, employing these species’ gross morphology and anatomy could scrutinise future evaluations and taxonomic placements.